The History (and Philosophy) of Religions - Rennie, Bryan (Studies in religion, 2012)
In a paper given at a Roundtable at the American Academy of Religion (AAR) National Annual Conference in Montreal in November of 2009, jointly organized by the North American Association for the Study of Religion and the Critical Theory and Discourses in Religion Group of the AAR, I argued for the ineluctably philosophical nature of what is most commonly called ‘method and theory in the study of religion.’ That paper (Rennie, 2010) also argues that what is conventionally referred to as ‘philosophy of religion’ does not, strictly speaking, warrant that name since it is in fact a form of theology that utilizes philosophical methodologies to consider principally, if not exclusively, Christian concerns. I also argued that a philosophy of religion(s) constituted along the lines of the philosophy of science would be a potential improvement in both ‘philosophy of religion’ and ‘method and theory in the study of religion.’ In this paper I would like to consider—with the help of a closer look at contemporary philosophy of science—precisely what a reconstituted history (and philosophy) of religions might look like, how it might differ from current scholarship, and what it might achieve. Dans une communication donnée lors d’une table ronde à l’American Academy of Religion (AAR) National Annual Conference à Montréal en novembre 2009, organisée conjointement par le North American Association for the Study of Religion et le groupe de Critical Theory and Discourses in Religion de l’AAR, j’avais argué la nature inéluctablement philosophique de ce qui est couramment appelé « Method and Theory in the Study of Religion ». Cet article (Rennie, 2010) soutient également la thèse que ce qu’on appelle couramment « Philosophie de la religion » ne correspond pas stricto sensu à ce qu’une telle dénomination recouvre puisqu’il s’agit en fait d’une forme de théologie recourant à des méthodes philosophiques pour envisager des préoccupations principalement, sinon exclusivement, chrétiennes. Je soutiens aussi qu’une philosophie des religions constituée à partir des lignes de force de la philosophie des sciences pourrait apporter une amélioration potentielle de la philosophie de la religion, de la méthode et de la théorie dans l’étude des religions. Dans cet article, j’aimerais examiner précisément —par le biais des apports de la philosophie des sciences contemporaine— ce à quoi l’histoire (et la philosophie) des religions pourrait ressembler, les termes dans lesquels elle se distinguerait des approches actuelles et ce à quoi nous pourrions ainsi aspirer.